Perbandingan Penggunaan Media Audio Visual dan Media Cetak Terhadap Kemampuan Membaca Surah-Surah Pendek Peserta Didik Kelas III MIN Sepabatu Tinambung Kabupaten Polewali Mandar - Nur Anisa; Ilyas Ismail; Andi Halimah (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
ABSTRACT (ENGLISH) This study aims to (1) determine the ability of reading short chapters at third grade students of MIN Sepabatu Tinambung Polewali Mandar Regency who were using audio-visual media; (2) find out the ability of reading short chapters at class III students of MIN Sepabatu Tinambung Polewali Mandar Regency who were using print media; (3) find out the comparison of the ability of reading short surah of students between those taught using print media at class III MIN Sepabatu Tinambung Polewali Mandar Regency. The type of research that used in this study was a comparative experiment. The population in this study were all third grade students consisting of 3 study groups totaling 54 students with a total sample of 38. The sampling technique that used was multiple random sampling. The research instrument that used was a test in the form of a practice test for reading the Qur'an. The data analysis technique that used was descriptive statistical analysis technique and inferential statistical analysis technique through SPSS v.16 for windows application. The results obtained in the two classes through descriptive analysis, namely for the experimental class 1 (audio-visual media) the average pre-test value was 65.8 and the post-test average was 86.6, while for the experimental class 2 (printed media) the average pre-test score is 59.3 and the post-test average is 77.1. The results of the inferential data analysis showed that the significance value obtained was tcount = 3.566 > ttable = 2.042 and the level value was sig. (2-tailed) = 0.001 < 0.005, which means H1 is accepted and H0 is rejected. So it can be concluded that there is a significant difference from the using of audio-visual media and print media on the ability of reading short suras of class III students at MIN Sepabatu Tinambung, Polewali Mandar Regency. The implication of this research is that teachers can generate creativity in designing, using and maximizing the quality of learning by using learning media in the classroom in order to support the effective use of audio-visual media and print media, and can be a foundation in carrying out learning to read the Qur'an. ABSTRAK (INDONESIA) Penelitian ini bertujuan untuk (1) Mengetahui kemampuan membaca surah-surah pendek peserta didik kelas III MIN Sepabatu Tinambung Kab. Polewali Mandar yang diajar dengan menggunakan media audio visual; (2) Mengetahui kemampuan membaca surah-surah pendek peserta didik kelas III MIN Sepabatu Tinambung Kab. Polewali Mandar yang diajar dengan menggunakan media cetak; (3) Mengetahui perbandingan kemampuan membaca surah-surah pendek peserta didik antara yang diajar dengan menggunakan media audio visual dan yang diajar dengan menggunakan media cetak kelas III MIN Sepabatu Tinambung Kab. Polewali Mandar. Jenis penelitian yang digunakan dalam penelitian ini adalah eksperimen komparatif. Populasi dalam penelitian ini seluruh peserta didik kelas III terdiri dari 3 rombongan belajar berjumlah 54 peserta didik. Teknik pengambilan sampel yang digunakan adalah multiple random sampling. Instrumen penelitian yang digunakan adalah tes berupa tes praktik membaca al-Qur’an. Teknik analisis data yang digunakan adalah analisis statistik deskriptif dan analisis statistik inferensial melalui aplikasi SPSS v.16 for windows. Hasil penelitian yang diperoleh pada kedua kelas tersebut melalui analisis deskriptif untuk kelas eksperimen 1 diperoleh nilai rata-rata pre-test 65,8 dan nilai rata-rata post-test 86,6, sedangkan kelas eksperimen 2 diperoleh nilai rata-rata pre-test 59,3 dan nilai rata-rata post-test 77,1. Hasil analisis inferensial data menunjukkan bahwa nilai signifikansi yang diperoleh thitung = 3,566 > ttabel = 2,042 dan nilai taraf sig. (2-tailed) = 0,001 < 0,005, berarti H1 diterima dan H0 ditolak. Sehingga dapat disimpulkan terdapat perbedaan yang signifikan dari penggunaan media audio visual dan media cetak terhadap kemampuan membaca surah-surah pendek peserta didik kelas III MIN Sepabatu Tinambung Kabupaten Polewali Mandar.